DEVICE STUDYING THE WEAR PROCESS OF DIFFERENT MATERIALS - Dadakhanov, Nurilla (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Corrosion occurs as a result of friction between moving parts of machines, which leads to the destruction of surfaces. As a result, the dimensions of parts change and the deviation from the required technical and technological indicators increases. Practice and research studies have shown that friction and excision intervals are the main cause of frictional and excited intersection failure. Special devices for studying wear of surfaces in gears and sliding surfaces of machines have been studied. A simple design of a device that studies wear under laboratory conditions is proposed.